Analisis Kinerja Keuangan PT Adaro Energy Tbk Periode 2019 – 2023 - Fikri Rijali, Nadi (Jurnal PubBis, 2025)
Financial issues are one of the most vital concerns for companies in business development across all industries. A company's financial performance can be interpreted as its prospects or future, growth, and good development potential. Financial performance evaluation can be conducted using financial statement analysis, which allows financial managers and interested parties to quickly assess financial conditions. This is because the presentation of financial ratios indicates the health of a company. The purpose of this research is to understand and analyze the financial performance of PT Adaro Energy Tbk based on Financial Ratios. Specifically, the objectives of this study are to: Analyze the financial performance of PT Adaro Energy Tbk based on Liquidity Ratios, Profitability Ratios, and Solvency Ratios. The research method used is descriptive quantitative, as this study involves analyzing the financial statements of PT Adaro Energy Tbk. The method includes collecting, classifying, analyzing, and interpreting data related to the company's current issues, as well as comparing them with the actual situation to draw conclusions. The population in this study is PT Adaro Energy Tbk from 2019-2023. The research results show that the Financial Performance Analysis of PT Adaro Energy Tbk, based on Liquidity Ratios, falls into the "Very Healthy" category. Based on Profitability Ratios, it falls into the "Quite Healthy" category, and based on Solvency Ratios, it falls into the "Healthy" category. The implications of this research can serve as a basis for investors, management, and other stakeholders in making investment decisions, evaluating company performance, assessing risks, and planning policies related to the mining and energy industry